Competing Visions of India in World Politics : India's Rise Beyond the West - Sullivan, Kate, 1980- (New York, NY : Palgrave Macmillan, 2015)
'Competing Visions of India in World Politics: India's Rise Beyond the West presents an alternative set of reflections on India's contemporary global role to those narrated by mainstream, US-centric accounts within International Relations. Collectively, the contributors explore a spectrum of non-Western perspectives on India's growing international influence. They deliver insights into a range of shared global issues, processes and institutions, including climate change, development cooperation, UN Security Council reforms, nuclear politics and the terms of world trade. Together, these readings provide a critical evaluation of India's success in reconciling a quest for recognition from established major powers with a desire to maintain relations of solidarity with developing country allies of the Cold War era. This volume is essential reading for anyone studying rising powers, BRICS countries, global power shifts and South-South linkages and will appeal to students and scholars of non-Western International Relations, Global Studies and International Development'--
Machine generated contents note: -- Introduction: Creating Diversity in Contemporary Readings of India's Global Role; Kate Sullivan 1.India's Ambivalent Projection of Self as a Global Power: Between Compliance and Resistance; Kate Sullivan 2. Chinese Views of a Nuclear India: From the 1974 Peaceful Nuclear Explosion to the Nuclear Suppliers Group Waiver in 2008; Nicola Horsburgh 3.India in Climate Change: The View from Tokyo; Yuka Kobayashi 4.Just Another Regional Superpower? A Cautious South Korea Watches India's Rise; Danielle Chubb 5.From Imperial Subjects to Global South Partners: South Africa, India, and the Politics of Multilateralism; Christopher J. Lee 6.What does'Development Cooperation' Mean? Perceptions from Africa and India; David Harris and Simona Vittorini 7.The'Eastern Brother': Brazil's View of India as a Diplomatic Partner in World Trade; Vini;cius Rodrigues Vieira 8.'The Other Pacifist': Mexican Views on India's Quest for Great Power Status; Gilberto Estrada Harris 9.India in the Iranian imagination: Between Culture and Strategic Interest; Arshin Adib-Moghaddam 10. Views of India from the Conflicting Parties in Syria; Omar Sharaf 11. Russian Views of India in the Context of Afghanistan; Natasha KuhrtConclusion; Kate Sullivan.
Includes bibliographical references (pages 202-228) and index.
Keywords: India -- Foreign relations